Pemahaman dan Implementasi Nilai-Nilai Pancasila di Kalangan Siswa Kelas 11 SMA Bina Dharma (Indo-MathEdu Intellectuals Journal, 2024)
This study examines the understanding and implementation of Pancasila values among 11th-grade students at SMA Bina Dharma using a qualitative approach and case study method. The research subjects, selected through purposive sampling, are 11th-grade students considered mature enough to comprehend Pancasila values. Data were collected through observation, in-depth interviews, and documentation, then analyzed using thematic analysis and triangulation to ensure validity. The results show that students' understanding tends to be theoretical and superficial, due to less interactive teaching methods and a lack of activities linking theory to real-world practice. It is necessary to integrate Pancasila values into the curriculum, employ more interactive teaching methods, and foster cooperation with families and communities to enhance the understanding and practice of Pancasila values in schools.